2020
DOI: 10.1111/1744-9987.13541
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evaluation of processed ascites in patients undergoing cell‐free and concentrated ascites reinfusion therapy

Abstract: The biochemical composition of processed ascites is not well researched and may differ among institutions. This prospective study was conducted to evaluate the biochemical characteristics of processed ascites of 11 patients with liver cirrhosis and carcinoma who underwent cell‐free and concentrated ascites reinfusion therapy. The ascites due to carcinoma were more acidic and had higher lactate dehydrogenase activity than those due to liver cirrhosis. The ascites due to liver cirrhosis contained a higher amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In contrast, the IL-6 concentrations were reported to decrease with filtration and concentration processes during CART (25). While the reason for the discrepancy in proinflammatory cytokine levels remains unclear, differences in the reinfusion rate of the processed ascitic fluid across the studies are a possibility (10) (26,27). The infusion of IL-6 over a short period of time stimulates immune responses such as a rise in body temperature (25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the IL-6 concentrations were reported to decrease with filtration and concentration processes during CART (25). While the reason for the discrepancy in proinflammatory cytokine levels remains unclear, differences in the reinfusion rate of the processed ascitic fluid across the studies are a possibility (10) (26,27). The infusion of IL-6 over a short period of time stimulates immune responses such as a rise in body temperature (25).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with decompensated cirrhosis who develop large volumes of ascitic fluid notice abdominal distention, which may markedly impair the patients' quality of life (4). Evidencebased clinical practice guidelines for liver cirrhosis have shown that diuretic resistance or poor diuretic response is an indication for large abdominal paracentesis or cell-free and concentrated ascites reinfusion therapy (CART) (5,6), with fever, high blood pressure, headache, and shaking with chills having been reported as CART-related adverse events (7). Most patients experience high fever during the reinfusion of ascitic fluid (8), with evidence implicating endotoxin or inflammatory cytokines as a cause (9).…”
mentioning
confidence: 99%